Produksi Enzim Amilolitik dari Bacillus megaterium Menggunakan Variasi Kadar Pati Sagu (Metroxylon sp.) - Sandra Madonna (Department of Biology, Faculty of Science and Technology, Syarif Hidayatullah State Islami, 2014)
The application of enzymes as biocatalysts for the industries in Indonesia has increased. Among the enzymes that are needed in Indonesia, one of which amylolytic enzymes. Amylolytic enzymes constitute a group of enzymes that catalyze the hydrolysis of starch into simple sugars consisting of glucose units. In this study amylolytic enzyme isolated from the bacterium Bacillus megaterium. Enzyme production was submerged fermentation method for 14 hours using sagostarch Metroxylon sp. varies. Measurement of enzyme activity was determined by the method amylolytik Somogy-Nelson. Research results showed that2 % (w/v) of sago starchis the optimum consentration in media with highest amylolytic enzyme activity that is equal to 0.076 units/ml and sugar medium formed by181.254ug/ml in the fermentation medium.